CHT, that sheds blood - Abedin, Zainal. 1951- (Dhaka, Bangladesh : Sunzida Anzuman : Distributor, Ramon Publishers, 1997)
On troubles in the Chittagong Hill Tracts District, Bangladesh and Chakmas.
Includes bibliographical references.
Keywords: Chakma (Asian people) -- Politics and government; Chittagong Hill Tracts (Bangladesh : Region) -- Politics and government -- 20th century